Investigation into the basement morphology and tectonic lineament using aeromagnetic anomalies of Parts of Sokoto Basin, North Western, Nigeria - G. Emujakporue; C.C. Ofoha; I. Kiani (Egyptian Journal of Petroleum)
This study, which spans latitude 5°N–5.30IN and Longitude 13°E–13.5°E with an approximate area of about 3400 km2 within the Northwestern Sokoto basin of Nigeria, aims to delineate possible source of stress regime, determining the structural features and their corresponding trend directions, delineating lithologic boundaries as evidenced by magnetic disturbances caused by different rock types and estimating the hydrocarbon viability within the study area by interpreting the behavior of the geophysical data obtained from the Nigeria Geological Survey Agency, NGSA in half degree sheet. The aeromagnetic data was subjected to both qualitative and quantitative analytical techniques using Oasis Montaj software, version 8.1. The result of the qualitative analysis generated some magnetic gradient maps showing dominant and minor magnetic structures trending E-W, NE-SW and NW-SE. These trends are possible fault indicators within the region. Similarly, the qualitative analysis revealed lithologic boundaries trending in the E-W and NW-SE direction. The dominant E-W trend possibly highlights the stress regime and also represents the Pre-Pan African Orogeny that was characterized by small brittle deformation which resulted in the development of conjugate strike-slip fault systems while the truncated NE-SW, NW-SE trends indicate Pan-African Orogeny. On the other hand, quantitative analysis performed on the aeromagnetic data by means of Source Parameter Imaging (SPI) quantitative method reveals depth to deep seated magnetic sources to range from 54.1 m to 3384.4 m but with an average of about 739 m. The dominant E-W tectonic magnetic trending structures and a thickness average of 739 m limit the possibility of oil and gas exploration. Thus the possibility of hydrocarbon exploration even when seismic sections are run within the study area will be very minimal. Keywords: Sokoto basin, Pre-Pan African Orogeny, Pan African Orogeny, Euler deconvolution, Source parameter imaging (SPI)